High Degree of Accuracy of a Novel Image‐free Handheld Robot for Unicondylar Knee Arthroplasty in a Cadaveric Study. Issue 1 (January 2015) - Lonner, Jess H.; Smith, Julie R.; Picard, Frederic; Hamlin, Brian; Rowe, Philip J.; Riches, Philip E.
Abstract: Background: Surgical robotics has been shown to improve the accuracy of bone preparation and soft tissue balance in unicondylar knee arthroplasty (UKA). However, although extensive data have emerged with regard to a CT scan‐based haptically constrained robotic arm, little is known about the accuracy of a newer alternative, an imageless robotic system. Questions/purposes: We assessed the accuracy of a novel imageless semiautonomous freehand robotic sculpting system in performing bone resection and preparation in UKA using cadaveric specimens. Methods: In this controlled study, we compared the planned and final implant placement in 25 cadaveric specimens undergoing UKA using the new tool. A quantitative analysis was performed to determine the translational, angular, and rotational differences between the planned and achieved positions of the implants. Results: The femoral implant rotational mean error was 1.04° to 1.88° and mean translational error was 0.72 to 1.29 mm across the three planes. The tibial implant rotational mean error was 1.48° to 1.98° and the mean translational error was 0.79 to 1.27 mm across the three planes. Conclusions: The image‐free robotic sculpting tool achieved accurate implementation of the surgical plan with small errors in implant placement. The next step will be to determine whether accurate implant placement translates into a clinical and functional benefit for the patient.